Oligocene tuffs at Domžale, the Ljubljana basin, Slovenia - Kralj, Polona (Geologija, 2000)
Oligocene volcanics have not been found yet in the Ljubljana basin. At Domžale, fine-grained tuffs predominate, although coarse-grained and lapilli tuffs also occur. The main constituents are volcanic glass shards. The tuffs are rhyolitic in composition. Alteration is reflected in the development of clay minerals - calcic montmorillonite and illite.
Keywords: Domžale; klastične kamnine; oligocen; predornine; vulkanske kamnine